This I Believe - Tsiang, Tingfu F. (Tingfu Fuller) (Tufts Archival Research Center, 2006)
Tinfu Tsiang describes his belief that China and the West each have valuable cultural insight to offer the other, and that the way to world peace is to focus on ulitizing existing resources more efficiently and to preserve human freedom in one's home country.